Activated nitrogen doped graphene shell towards electrochemical oxygen reduction reaction by its encapsulation on Au nanoparticle (Au@N-Gr) in water-in-oil ``nanoreactors'' - Dhavale, Vishal M.; Gaikwad, Sachin S.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2014)
Encapsulation of nitrogen doped graphene on Au nanoparticle (Au@N-Gr) could be accomplished through a water-in-oil emulsion technique, where the emulsion droplets act as `nanoreactors' and the redox reaction inside the droplets results in the formation of core-shell nanoparticles. The encapsulation of N-Gr on a small quantity of Au (N-Gr : Au wt ratio of 90 : 10) made the N-Gr layer more conductive and active towards electrochemical oxygen reduction reaction (ORR). The enhanced conductivity helped the system narrow down the ohmic overpotential, and direct electronic interactions between the Au and Gr layers brought in a favourable positive shift to the onset potential for ORR. Encapsulation has helped N-Gr reduce the overpotential by similar to 121 mV as compared to N-Gr alone. Apart from this, the oxygen reduction kinetics of Au@N-Gr also appeared to be superior to N-Gr and Au nanoparticles as separate entities due to greater involvement of the preferred 4-electron reduction pathway. At -0.3 V (vs. Hg/HgO), the percentage of hydrogen peroxide (H2O2) (a product formed from the undesirable 2-electron reduction pathway) was found to be 16.5% for Au@Gr, where Au was covered with undoped Gr, which gets reduced to a significantly low level of 6.5% for Au@N-Gr. Au and N-Gr as separate entities give yield of H2O2 as 52.2 and 47.7%, respectively. From these, it can be concluded that the coverage of N-Gr on Au helps decrease the yield of H2O2 drastically apart from the benefits of synergistic interactions in reducing both ohmic and activation overpotentials.

Nitrogen-doped graphene interpenetrated 3D Ni-nanocages: efficient and stable water-to-dioxygen electrocatalysts - Dhavale, Vishal M.; Gaikwad, Sachin S.; George, Leena; Devi, R. Nandini; Kurungot, Sreekumar (Nanoscale, 2014)
Herein, we report the synthesis of a nitrogen-doped graphene (NGr) interpenetrated 3D Ni-nanocage (Ni-NGr) electrocatalyst by a simple water-in-oil (w/o) emulsion technique for oxidation of water to dioxygen. Correlation of adsorption of NGr and subsequent interpenetration through the specific surface plane of nickel particles as well as the concomitant interaction of N and C with Ni in the nano-regime has been investigated. Apart from the benefits of the synergistic interactions between Ni, N, and C, the overall integrity of the structure and its intra-molecular connectivity within the framework help in achieving better oxygen evolution characteristics at a significantly reduced overpotential. The engineered Ni-NGr nanocage displays a substantially low overpotential of similar to 290 mV at a practical current density of 20 mA cm(-2) in 0.1 M KOH. In comparison, NGr and Ni-particles as separate entities give overpotentials of similar to 570 and similar to 370 mV under similar conditions. Moreover, the long term stability of Ni-NGr was investigated by anodic potential cycling for 500 cycles and an 8.5% increment in the overpotential at 20 mA cm(-2) was observed. Additionally, a chronoamperometric test was performed for 15 h at 20 mA cm(-2), which highlights the better sustainability of Ni-NGr under the actual operating conditions. Finally, the quantitative estimation of evolved oxygen was monitored by gas chromatography and was found to be 70 mmol h(-1) g(-1) of oxygen, which is constant in the second cycle as well.

Nanocrystalline Fe-Fe2O3 particle-deposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2015)
The size-controlled growth of nanocrystalline Fe-Fe2O3 particles (2-3 nm) and their concomitant dispersion on N-doped graphene (Fe-Fe2O3/NGr) could be attained when the mutually assisted redox reaction between NGr and Fe3+ ions could be controlled within the aqueous droplets of a water-in-oil emulsion. The synergistic interaction existing between Fe-Fe2O3 and NGr helped the system to narrow down the overpotential for the oxygen reduction reaction (ORR) by bringing a significant positive shift to the reduction onset potential, which is just 15 mV higher than its Pt-counterpart. In addition, the half-wave potential (E-1/2) of Fe-Fe2O3/NGr is found to be improved by a considerable amount of 135 mV in comparison to the system formed by dispersing Fe-Fe2O3 nanoparticles on reduced graphene oxide (Fe-Fe2O3/RGO), which indicates the presence of a higher number of active sites in Fe-Fe2O3/NGr. Despite this, the ORR kinetics of Fe-Fe2O3/NGr are found to be shifted significantly to the preferred 4-electron-transfer pathway compared to NGr and Fe-Fe2O3/RGO. Consequently, the H2O2% was found to be reduced by 78.3% for Fe-Fe2O3/NGr (13.0%) in comparison to Fe-Fe2O3/RGO (51.2%) and NGr (41.0%) at -0.30 V (vs. Hg/HgO). This difference in the yield of H2O2 formed between the systems along with the improvements observed in terms of the oxygen reduction onset and E-1/2 in the case of Fe-Fe2O3/NGr reveals the activity modulation achieved for the latter is due to the coexistence of factors such as the presence of the mixed valancies of iron nanoparticles, small size and homogeneous distribution of Fe-Fe2O3 nanoparticles and the electronic modifications induced by the doped nitrogen in NGr. A controlled interplay of these factors looks like worked favorably in the case of Fe-Fe2O3/NGr. As a realistic system level validation, Fe-Fe2O3/NGr was employed as the cathode electrode of a single cell in a solid alkaline electrolyte membrane fuel cell (AEMFC). The system could display an open circuit voltage (OCV) of 0.73 V and maximum power and current densities of 54.40 mW cm(-2) and 200 mA cm(-2), respectively, which are comparable to the performance characteristics of a similar system derived by using 40 wt% Pt/C as the cathode electrode.

Nanocrystalline Fe-Fe2O3 particledeposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2017)